2017
DOI: 10.3233/jpd-161015
|View full text |Cite
|
Sign up to set email alerts
|

Physical Therapy Versus a General Exercise Programme in Patients with Hoehn Yahr Stage II Parkinson’s Disease: A Randomized Controlled Trial

Abstract: Physiotherapy seems to be more effective than a generic exercise programme in patients with Hoehn Yahr stage II PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(39 citation statements)
references
References 25 publications
1
38
0
Order By: Relevance
“…This study showed that short active motor rehabilitation programs provide substantial functional benefit for patients with PD in improving their quality of life. This supports previously observed positive effects of different rehabilitation methods in PD [ 46 , 47 ]. It was already shown that exercise enhances the efficacy of dopamine substituting compounds, probably as a result of an improved endogenous dopamine release [ 48 ].…”
Section: Discussionsupporting
confidence: 92%
“…This study showed that short active motor rehabilitation programs provide substantial functional benefit for patients with PD in improving their quality of life. This supports previously observed positive effects of different rehabilitation methods in PD [ 46 , 47 ]. It was already shown that exercise enhances the efficacy of dopamine substituting compounds, probably as a result of an improved endogenous dopamine release [ 48 ].…”
Section: Discussionsupporting
confidence: 92%
“…It was created in 1967 and is still one of the most widely used tools in the evaluation of Parkinson's disease patients Its development was based on the observation of 856. people. It is presented as follows: 1 -unilateral damage without functional impairment, 2 -bilateral or moderate damage without balance disorders, 3 -impaired balance and function not preventing independent living, disability is slight or moderate, 4 -fully developed disease, disability is significant, although the patient is still able to stand up and walk independently, 5 -the patient is in a wheelchair or in bed [37]- [41] To standardize the scale, half-points of 1.5 and 2.5 were introduced (Unified Parkinson's Disease Rating Scale -UPDRS). The described scale, in determining the severity of the disease is directed at assessing the patient's posture, and for this reason, does not reflect other accompanying dysfunctions of the patient (Figure 4.)…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have focused on the improvement of motor symptoms in patients with PD. For example, Dipasquale et al (2017) randomly allocated 40 patients with PD of HY stage 2 to the following two groups: one followed a general exercise (GE) program, and one followed a physical therapy (PT) program. Outcome indicators included the Functional Independence Measure, Hamilton Rating Scale, Timed Up & Go test, and Unified Parkinson’s Disease Rating Scale (UPDRS) score, which were all significantly better for the PT group when compared with the GE group at the end of treatment.…”
Section: Discussionmentioning
confidence: 99%